A representatividade da mulher nos livros didáticos de geografia e documentos curriculares oficiais - Campos, Mariana Brockes Campos (2023)
The gender discussion is current and very relevant to society, geography and teaching. When thinking about this, the present dissertation aims to understand the different forms of representation of women in Geography textbooks for Elementary School - final years, approved by the last PNLD public notice and in the curricular documents that involve textbooks and educational education. geographic. As the specific objectives, identify the gender approaches that govern education (the LDB, BNCC and PNLD) and imply the textbook; understand the instituting elements of the representation of women in the contents of textbooks and develop proposals for subverting the gender order found in textbooks. Considering that textbooks carry great educational value for Brazilian education because they are widely distributed to schools throughout Brazil, understanding how they represent women is understanding which ideas tend to be perpetuated by education. Therefore, the collection most distributed by the 2020 PNLD was analyzed qualitatively and quantitatively, with the intention of understanding if and how women are represented. It was found that women have a smaller number of representations in the images of textbooks. Only about 20% of all images are female representations. The representations of females regarding the content are also not sufficient for us to consider that they seek to promote gender equality. It was noticed that women tend to occupy the same type of space, which is culturally devalued, such as rural, craft, family, basic industries and with little protagonism. It was found that educational curriculum documents are also scarce when it comes to female representation, mentioning gender issues a few times and comparatively, between documents over the years, gender issues have suffered many deletions in terms of gender equality, therefore, thus aligning with the lack of promotion of gender equality in Geography textbooks. It is expected that this research can contribute to a construction of a more critical analysis at Geography, textbooks and curriculum, from a gender perspective.